Aplasia cutis congenita: three cases with three different underlying etiologies - Mihçi, Ercan; Erişir, Seyhan; Taçoy, Sükran; Lüleci, Güven; Alpsoy, Erkan; Oygür, Nihal (The Turkish Journal of Pediatrics, 2009)
Aplasia cutis congenita (ACC) is an uncommon condition in which localized or widespread areas of skin are absent or scarred at birth. There is no single underlying cause of ACC, as it simply represents a physical finding that reflects a disruption of intrauterine skin development. Here we report three cases of ACC of the scalp with three different etiologies: congenital rubella syndrome, trisomy 13 and fetal valproate syndrome. The aim of the present report is to increase awareness of these skin defects and emphasize the importance of underlying etiologies.